2016
DOI: 10.1136/bcr-2016-214802
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism as a side effect of infliximab

Abstract: We present a case of a 64-year-old man with Crohn's disease who developed parkinsonism after starting treatment with infliximab (Remicade). The patient had a 30-year history of Crohn's disease with previous surgical procedures and treatment with methotrexate. Treatment was augmented with infliximab, and 3 days after the first dose of 400 mg, a resting tremor began in the left leg. Over 4 months, symptoms progressed and now involved the right leg as well as both hands. There was no clinical effect of infliximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They can be classified as the pro-inflammatory ones that enhance the activities of lymphocytes to boost or to drive inflammation, and their anti-inflammatory counterparts that negatively regulate these activities. Hence, to orchestrate the cytokines profiling, such as Infliximab targeting TNF-α blockage, has been a novel and effective strategy to control the severity of IBD, though it always accompanies with multiple side effects ( Shah et al, 2014 ; Yilmaz et al, 2014 ; Henriksen and Eriksson, 2016 ). IL-4, IFN-γ, IL-12p70, and IL-17A are considered as pro-inflammatory cytokines that are produced excessively and chronically and they contribute greatly to the inflammatory reaction in IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be classified as the pro-inflammatory ones that enhance the activities of lymphocytes to boost or to drive inflammation, and their anti-inflammatory counterparts that negatively regulate these activities. Hence, to orchestrate the cytokines profiling, such as Infliximab targeting TNF-α blockage, has been a novel and effective strategy to control the severity of IBD, though it always accompanies with multiple side effects ( Shah et al, 2014 ; Yilmaz et al, 2014 ; Henriksen and Eriksson, 2016 ). IL-4, IFN-γ, IL-12p70, and IL-17A are considered as pro-inflammatory cytokines that are produced excessively and chronically and they contribute greatly to the inflammatory reaction in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current remedies have been designed to directly control or remiss the inflammatory response of IBD, which is mainly a combination of anti-inflammatory agents (such as sulfasalazine and mesalazine), glucocorticosteroids, immunomodulating drugs (including azathioprine, methotrexate, and cyclosporine), and more recently the biological neutralizer (like infliximab, adalimumab, and certolizumab). Nevertheless, physicians and researchers keep seeking resolutions for IBD due to the unsatisfied efficacy and adverse drug reactions, such as parkinsonism, gastrointestinal, and liver adverse effects ( Rogler, 2010 ; Yilmaz et al, 2014 ; Henriksen and Eriksson, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that older patients with IBD had higher risk of PD which suggested that the age at IBD diagnosis might be a risk factor of PD. We also noticed that some studies presented the medication-associated side effects which resembled parkinsonism in the older population 8 9. Therefore, it is necessary to take it into consideration whether older people will take more medications, and whether these medications lead to a higher risk of PD also needs further studies to verify in the future.…”
mentioning
confidence: 99%